2019
DOI: 10.1108/ijwhm-10-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of education program on hospital waste management

Abstract: Purpose The purpose of this paper is to assess the effectiveness of Kuwait Infection Control Directorate educational program in improving knowledge, attitude and practices (KAP) of environmental service workers (ESWs) regarding the management of infectious and sharps waste. Design/methodology/approach An interventional educational pre-test/post-test study was conducted over seven months, on a sample of 102 ESWs in Farwaniya General Government Hospital, Kuwait. Educational sessions and practical training usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Likewise, Kumar et al [21] assessed the effectiveness of an intensive training program in HCW management in Pakistan, showing that training is an effective method to improve knowledge, attitudes and practices among healthcare personnel regarding infectious waste management. Along the same lines is the study by Abdo et al [22], which showed the improvements provided by an educational program in the management of infectious and sharps waste in Kuwait.…”
mentioning
confidence: 78%
“…Likewise, Kumar et al [21] assessed the effectiveness of an intensive training program in HCW management in Pakistan, showing that training is an effective method to improve knowledge, attitudes and practices among healthcare personnel regarding infectious waste management. Along the same lines is the study by Abdo et al [22], which showed the improvements provided by an educational program in the management of infectious and sharps waste in Kuwait.…”
mentioning
confidence: 78%
“…This contribute to individuals' attitudes and perceived behavioral control regarding waste management. Training and Education enhances individuals' skills, knowledge, and attitudes toward waste management practices (Abdo et al, 2019). Training and education alter perceived behavioral control and attitudes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Sixteen articles assessed the effectiveness of multi-component educational interventions [40,42,43,46,[51][52][53][54][55][56][57][58][59][60][61][62], which had durations ranging from 15 min to 1 year (Table 1). Experienced instructors, physicians, or nurses; the department of microbiology and infection control; and the company responsible for waste management delivered the interventions [43,46,55,57].…”
Section: Multi-component Educational Interventionsmentioning
confidence: 99%
“…Experienced instructors, physicians, or nurses; the department of microbiology and infection control; and the company responsible for waste management delivered the interventions [43,46,55,57]. The effectiveness of multi-component educational interventions was evaluated immediately in four studies [51,57,60,61], in a period of less than two months in two studies [46,59], and after three months in four studies [40,43,52,56], while a long-term assessment (from four to 18 months) was reported in five articles [53,54,58,61,62].…”
Section: Multi-component Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation